Enhanced salt-tolerance of Bacillus subtilis glutaminase by fusing self-assembling amphipathic peptides at its N-terminus - Liu, Song; Rao, Shengqi; Chen, Xiao; Li, Jianghua (Frontiers in Bioengineering and Biotechnology, 2022)
Glutaminase (EC 3.5.1.2) can catalyze the deamidation of glutamine, which has been used to improve umami taste in oriental fermented foods. However, a high salt concentration is still a fundamental challenge for glutaminase application, especially in soy sauce production. To improve the salt tolerance of glutaminase, the self-assembling amphiphilic peptides EAK16 and ELK16 were fused to the N-terminus of a mutant (E3C/E55F/D213T) derived from Bacillus subtilis glutaminase, yielding the fusion enzymes EAK16-E3C/E55F/D213T and ELK16-E3C/E55F/D213T, respectively. As ELK16-E3C/E55F/D213T was expressed as insoluble active inclusion bodies, only the purified EAK16-E3C/E55F/D213T was subjected to further analyses. After the incubation with 18% (w/v) NaCl for 200 min, the residual activities of EAK16-E3C/E55F/D213T in a NaCl-free solution reached 43.6%, while E3C/E55F/D213T was completely inactivated. When the enzyme reaction was conducted in the presence of 20% NaCl, the relative activity of EAK16-E3C/E55F/D213T was 0.47-fold higher than that of E3C/E55F/D213T. As protein surface hydrophobicity and protein particle size analysis suggested, oligomerization may play an important role in the salt-tolerance enhancement of the fusions. Furthermore, EAK16-E3C/E55F/D213T achieved a 0.88-fold increase in the titer of glutamic acid in a model system of soy sauce fermentation compared to E3C/E55F/D213T. Therefore, the fusion with self-assembling amphiphilic peptides is an efficient strategy to improve the salt-tolerance of glutaminase.